Neuroprotective effects of antioxidative flavonoids, quercetin, (+)-dihydroquercetin and quercetin 3-methyl ether, isolated from Opuntia ficus-indica var. saboten - Dok-Go, H; Lee, HH; Kim, HJ; Lee, EH; Lee, JY; Song, YS; Lee, YH; Jin, CB; Lee, YS; Cho, J (ELSEVIER SCIENCE BV, 2003)
The flavonoids quercetin, (+)-dihydroquercetin, and quercetin 3-methyl ether were isolated from the ethyl acetate fractions of the fruits and stems of Opuntia ficus-indica var. saboten. In the present study, we evaluated their protective effects against oxidative neuronal injuries induced in primary cultured rat cortical cells and their antioxidant activities by using three different cell-free bioassays. Quercetin was found to inhibit H2O2- or xanthine (X)/xanthine oxidase (XO)-induced oxidative neuronal cell injury, with an estimated IC50 of 4-5 mug/ml. However, it was no more protective at concentrations of 30 mug/ml and above. (+)-Dihydroquercetin concentration-dependently inhibited oxidative neuronal injuries, but it was less potent than quercetin. On the other hand, quercetin 3-methyl ether potently and dramatically inhibited H2O2- and X/XO-induced neuronal injuries, with IC50 values of 0.6 and 0.7 mug/ml, respectively. All three principles markedly inhibited lipid peroxidation and scavenged 1,1-diphenyl-2-picrylhydrazyl free radicals. In addition, quercetin and quercetin 3-methyl ether were shown to inhibit XO activity in vitro, with respective IC50 values of 10.67 and 42.01 mug/ml. These results indicate that quercetin, (+)-dihydroquercetin, and quercetin 3-methyl ether are the active antioxidant principles in the fruits and stems of Opuntia ficus-indica var. saboten exhibiting neuroprotective actions against the oxidative injuries induced in cortical cell cultures. Furthermore, quercetin 3-methyl ether appears to be the most potent neuroprotectant of the three flavonoids isolated from this plant. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: RAT CORTICAL-NEURONS; LIPID-PEROXIDATION; ACORUS-GRAMINEUS; CACTUS; EXTRACT; MECHANISMS; RHIZOMES; DAMAGE; DNA